2008
DOI: 10.2135/cropsci2007.08.0432
|View full text |Cite
|
Sign up to set email alerts
|

Frogeye Leaf Spot of Soybean: A Review and Proposed Race Designations for Isolates of Cercospora sojina Hara

Abstract: Frogeye leaf spot (FLS), caused by Cercospora sojina K. Hara, is a common disease of soybean [Glycine max (L.) Merr.] in most soybean‐growing countries of the world. Significant yield losses of soybean (10–60%) have been attributed to FLS under hot and humid growing conditions. The FLS in the southern United States has been kept under control by planting resistant cultivars. Cercospora sojina is a dynamic pathogen with extensive virulence or race diversity. The current number of C. sojina isolates at the Unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
92
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(99 citation statements)
references
References 28 publications
1
92
0
6
Order By: Relevance
“…Today, the use of resistant cultivars is the most efficient and cost effective means of controlling frogeye leaf spot, and is the main disease control measure adopted in Brazil (MIAN et al, 2009). This pathogen has not been associated with disease in any other crop or weed host (MIAN et al, 2008).…”
Section: Introductionmentioning
confidence: 97%
“…Today, the use of resistant cultivars is the most efficient and cost effective means of controlling frogeye leaf spot, and is the main disease control measure adopted in Brazil (MIAN et al, 2009). This pathogen has not been associated with disease in any other crop or weed host (MIAN et al, 2008).…”
Section: Introductionmentioning
confidence: 97%
“…A doença tem sido esporádica e limitada a algumas regiões produtoras (Reis & Kimati (1973), causando porém, danos, à cultura da soja, que variam de 21 a 60% (Mian et al, 2008). O uso de cultivares resistentes, a partir da incorporação de alelos de resistência em cultivares comerciais susceptíveis, é o meio mais econômi-co e eficiente de controle da doença (Gravina et al, 2004).…”
Section: Introductionunclassified
“…In the United States, estimated soybean yield reductions caused by frogeye leaf spot ranged between 183 868 and 345 148 metric tons from 2006 to 2009 (Koenning & Wrather, 2010). The use of host resistance has been an economical way to manage frogeye leaf spot, but the development of new virulent races that overcome single genes for resistance (Rcs genes) has been a hindrance to developing cultivars with durable resistance to C. sojina (Athow et al, 1962;Ross, 1968;Phillips & Boerma, 1981;Mian et al, 2008). Application of foliar fungicides has been another method of managing frogeye leaf spot; however, C. sojina isolates with resistance to quinone outside inhibitor (QoI) fungicides have been reported recently (Zhang et al, 2012a).…”
Section: Introductionmentioning
confidence: 99%
“…Mian et al (2008) evaluated 98 C. sojina isolates from different countries on 12 differential soybean lines, and found that the majority of these isolates could be classified within 11 different race groups. Evaluating 50 C. sojina isolates from Ohio on 12 differential soybean lines, Cruz & Dorrance (2009) reported a total of 20 different pathotype groups.…”
Section: Introductionmentioning
confidence: 99%